Analysis of brain signals - Tan, Yi Bing (2014)
Our human brain is made up of billions of brain cells known as neurons that transmit and receive information by sending electrical impulses from one neuron to the next. All neurons are electrically excitable hence this process in turn, generate a great amount of electrical activity in our brain which can be measured using several functional imaging methods such as Electroencephalography (EEG) and Magnetoencephalography (MEG). These brain signals change throughout the day according to external situational stimulus and various activities undertaken by individuals. The numerous brainwave states include Gamma (30-70 Hz), Beta (13-30 Hz), Alpha (8-12 Hz), Theta (4-8 Hz) and Delta (0.5-4 Hz). It is observed that each particular state of brainwave changes the state of consciousness in us and has a very close relationship and diverse effect on the overall health condition. As such, this project involves a literature review mainly on the different kinds of brainwave and frequencies generated during different activities and in patients with Cancer and brain diseases for instance, Epilepsy, Parkinson’s disease and Schizophrenia. In addition, the area on external brainwave stimulation such as, Brainwave Entrainment (BWE), and its results on altering brain states have been thoroughly explored. The effects of BWE on improvement of health conditions have been carefully studied. Furthermore, comparisons on the Power Spectral Density (PSD) diagrams were executed between cases of healthy and unhealthy subjects and in turn, conclusions were drawn from the abnormalities in these PSD diagrams. Last but not least, this report includes my recommendations and suggestions for future work based on external brain stimulation with respect to health issues.